RECONSTRUCTING STUDENT’S LEARNING ACHIEVEMENT THROUGH REMEDIAL TEACHING PROGRAM - Wartono, Wartono; Sumarjono, Sumarjono; Batlolona, John Rafafy (EDUSAINS, 2018)
MEREKONSTRUKSI PRESTASI BELAJAR SISWA MELALUI PROGRAM PENGAJARAN REMEDIAL AbstractRemedial teaching is a re-learning for students who face learning difficulty. Many teachers forget to do this program aiming at reconstructing the student’s learning achievement. This work aimed to know the effectiveness of remedial teaching program to reach the mastery learning. This study used the design of mixed method explanatory. The data collection was done by using test technique of the quantitative data, while the qualitative data were collected by observation and documentation techniques. The instrument used to collect the quantitative data was test and to collect the qualitative data, the researchers conducted the direct observation and documentation. Based on the research results, the effectiveness of remedial teaching program to achieve the mastery learning for the physics subject was 57.89% so that the remedial teaching program was effective enough to be implemented. Subsequently, the remedial teaching was conducted in the form of special and private treatment. Its method is in accordance with the students’ need or type of difficulty. The method used in this research was direct learning with the peer tutor. Thereby, the remedial teaching program can be recommended to help the students to attain the mastery learning in the physics subject.AbstrakPengajaran remedial adalah pembelajaran ulang bagi siswa yang menghadapi kesulitan belajar. Banyak guru lupa untuk melakukan program ini dengan tujuan merekonstruksi pencapaian belajar siswa. Tujuan dari penelitian ini untuk mengetahui efektivitas program pengajaran remedial untuk mencapai hasil belajar yang baik. Penelitian ini menggunakan desain metode campuran explanatory. Pengumpulan data dilakukan dengan menggunakan teknik uji data kuantitatif, sedangkan data kualitatif dikumpulkan dengan teknik observasi dan dokumentasi. Instrumen yang digunakan untuk mengumpulkan data kuantitatif adalah tes dan untuk mengumpulkan data kualitatif, para peneliti melakukan observasi langsung dan dokumentasi. Berdasarkan hasil penelitian, efektivitas program pengajaran remedial untuk mencapai ketuntasan belajar mata pelajaran fisika sebesar 57,89% sehingga program pengajaran remedial cukup efektif untuk dilaksanakan. Selanjutnya, pengajaran remedial dilakukan dalam bentuk perlakuan khusus dan pribadi. Metodenya sesuai dengan kebutuhan atau jenis kesulitan siswa. Metode yang digunakan dalam penelitian ini adalah pembelajaran langsung dengan tutor sebaya. Dengan demikian, program pengajaran remedial dapat direkomendasikan untuk membantu siswa untuk mencapai penguasaan pembelajaran dalam mata pelajaran fisik.Permalink/DOI: http://dx.doi.org/10.15408/es.v10i1.7240